Designing Inclusive Extended Reality (XR): Heuristics for Developing Accessible Immersive Content for Students with Motor Impairments - Istiarsyah Istiarsyah; Francesco Ricci; Alessandra Russo (Journal Emerging Technologies in Education, 2026)
Background. Extended Reality (XR) technologies have become increasingly prominent in educational settings, providing immersive and interactive learning opportunities. However, students with motor impairments encounter significant challenges when engaging with XR content, especially due to the reliance on physical interaction mechanisms such as hand gestures or specialized controllers. These barriers limit their ability to fully participate in the immersive experience that XR technologies offer. Purpose. The purpose of this study is to develop and assess a set of heuristics for creating accessible XR content that caters specifically to students with motor impairments. This research aims to evaluate the effectiveness of these heuristics by examining how they impact usability, accessibility, and user satisfaction among individuals with motor impairments in real-world XR applications. Method. The study adopts a mixed-methods approach, incorporating usability testing, focus group discussions, and expert reviews to gather comprehensive data on the proposed heuristics. Participants with motor impairments are asked to interact with XR content designed using the newly developed accessibility heuristics. The research gathers both qualitative and quantitative data, including task completion times, error rates, and user satisfaction metrics. Results. Findings indicate that students with motor impairments exhibit significant improvements in task completion times, reduced error rates, and higher user satisfaction when interacting with XR content that incorporates the proposed accessibility heuristics. Adaptive input methods, such as voice commands and customizable controllers, are identified as particularly effective in enhancing accessibility and engagement. Conclusion. This study contributes to the field of XR accessibility by providing practical guidelines for developers aiming to create more inclusive educational content. It underscores the importance of inclusive design in XR systems, ensuring that all learners, regardless of physical abilities, can benefit from immersive educational experiences. The results of this study offer a foundation for future research focused on expanding accessibility in XR learning environments.